PENGOLAHAN SABUT KELAPA MENJADI ASAP CAIR DENGAN MENGGUNAKAN PROSES PIROLISIS - Badin, Yoseph Ratu; Abrina Anggraini, Sinar Perbawani; Yuniningsih, Susy (eUREKA : Jurnal Penelitian Teknik Sipil dan Teknik Kimia, 2017)
Often on rubber, plantation, when rubber processing occurs things are harmfull to the surrounding community, which is when the freezing of the latex using formic acid so it still feels a pungent odor. In rubber processing can be argued that it is the low quality of rubber processing.Similarly, the problems that occurred in the wood industry, it was found that low-quality wood structure, very fragile and unstable so easily broken and easily attacked by termites. Technology liquid smoke can be utilized to overcome the above problems by using the raw material. The function of liquid smoke from coconut fiber as a natural preservative in industrial non-food such as wood industry and rubber plantations. The purpose of this study was to determine the quantity and quality of liquid smoke from coconut fiber Commonly, the processing of liquid smoke is consists of 3 phases: Preparation of phyrolysis process raw materials (cleaning, chopping, drying and weighing), Stages of process of pyrolysis (heating using a temperature of 150 ° C, heating time 5 hours), Stages of product analysis using GC/ MS Hewlett Packar Gc 6890 MSD 5973 which equipped by data base system Chesstation (phenol and acid compound) and a pH meter. The result of this study showed that the quantity of liquid smoke from coconut fiber is 32.35% and the quality of its liquid smoke is shown by 2.97% of phenol content ,6.8% of acidity and 2.62 of pH. Keywords: Coconut fiber, Pyrolysis, Condensation, Liquid smoke